Antimicrobial resistance in the practice of primary care physicians: infection diagnosis - Laudy-Wiaderny, Hanna; Nitsch-Osuch, Aneta (Family Medicine & Primary Care Review, 2026)
The selection of appropriate specimens for diagnostic testing constitutes a critical step in the treatment process, as the data thus generated forms the foundation for evidence-based medical decisions. Rapid diagnostic tests play a vital role in the differential diagnosis of infections by enabling the confirmation of the disease cause while the patient is still in the clinic. Currently, in Poland, several rapid tests can be ordered at the primary care level, including the 4-in-1 SARS-CoV-2/influenza A+B/RSV test, the Strep-test, and a quantitative test for CRP protein levels. The swift differentiation of prevalent viral infections from those that may be bacterial enables more targeted therapies, resulting in a reduction in unnecessary antibiotic use. Implementing antibiotic therapy only when there is a strong rationale for it is crucial in the fight against antimicrobial resistance, a significant and growing threat to public health. This article highlights the significance of patient preparation and collection techniques, the importance of collaboration with microbiology laboratories, and the role of diagnostic tests in the daily practice of primary care physicians (PCPs) in Poland. The article highlights the benefits of accessible diagnostic tests and their positive impact on improving the quality of medical care. This is the second article in a series addressing the issue of antibiotic resistance in primary care settings.